Pengaruh Independent Board Of Commissioner, Profitability dan Growth Opportunity terhadap Firm Value - Azhara, Yarika; Nurbaiti, Beti; Ningrum, Endah Prawesti; Nuryati, Tutty; Yulaeli, Tri (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
The non-cyclical consumer goods sector is considered attractive for investors due to its stable demand and resilience in times of economic uncertainty. However, firm value in this sector can still fluctuate due to internal governance and performance factors. This study aims to examine the effect of the independent board of commissioners, profitability, and growth opportunity on firm value in non-cyclical consumer goods companies listed on the Indonesia Stock Exchange. The study uses a quantitative approach with panel data obtained from 46 companies over the 2020–2023 period. The analysis is conducted using panel data regression with the fixed effect model, following data transformation to address classical assumption issues. The findings reveal that the independent board of commissioners has a significant negative effect on firm value, suggesting that increased board independence does not automatically translate to higher investor confidence. On the other hand, profitability and growth opportunity show a significant positive effect, indicating that companies with stronger earnings performance and higher growth potential tend to have higher firm value. These results highlight the importance of effective governance and financial performance in enhancing firm value in the Indonesian consumer goods sector.